Respon Amina Wadud Terhadap Ulama Iran Berkaitan dengan Perempuan - Bahy Chemy Ayatuddin Assri (UIN Sunan Kalijaga Yogyakarta, 2022)
Abstrack: This paper attempts to explore Amina Wadud's response as a feminist figure to the justification of Iranian clerics, who in fact are dominated by men, for Islamic law relating to women, particularly in matters of divorce, polygamy, inheritance rights, and women's leadership. The position and role of Iranian women is determined by the clergy. The interpretation of religious texts often favors women, so that women's role is only in the family sector. Its interpretation tends to harm women. This interpretation comes because the clergy are dominated by men who are still hegemony by the patriarchal system. The approach used in this study is the historical-analytical approach. The result of the research is that the role of the clerics covers all sectors of society, even the dress code is regulated and limited. Ulama also play a role in interpreting religious texts, including Islamic law relating to women. Their interpretation is only for their own benefit. Amina Wadud disagrees with the gender biased interpretation. He emphasized that all verses must be revealed according to the time and situation in which they were revealed. However, the message contained is not limited to the time and historical setting. Abstrak: Tulisan ini berusaha mengupas respon Amina Wadud selaku tokoh feminis terhadap justifikasi ulama Iran yang notabanenya didominasi oleh kaum laki-laki terhadap hukum Islam yang berkaitan dengan perempuan, khususnya dalam hal perceraian, poligami, hak waris, dan kepemimpinan perempuan. Posisi dan peran perempuan Iran ditentukan oleh para ulama. Interpretasi teks agama sering memojokan perempuan, sehingga peran perempuan hanya di sektor keluarga. Interpretasinya cenderung merugikan kaum perempuan. Interpretasi ini datang karena ulama didominasi oleh laki-laki yang masih terhegemoni oleh sistem patriarki. Pendekatan yang digunakan dalam penelitian ini yaitu pendekatan historis-analitis. Hasil penelitian yaitu peran ulama-ulama meliputi semua sektor masyarakat, bahkan sampai tatacara berpakaian pun diatur dan dibatas. Ulama-ulama pun berperan dalam menginterpretasikan teks-teks agama, termasuk hukum Islam yang berkaitan dengan perempuan. Penafsiran mereka hanya untuk kepentingan sendiri. Amina Wadud tidak setuju dengan penafsiran yang bias gender. Ia menegaskan bahwa semua ayat harus dipaparkan menurut waktu dan situasi turunnya. Namun, pesan yang terkandung tidak terbatas pada waktu dan suasana sejarahnya.